‘To look until your head starts spinning’ - Franaszek, Andrzej (Werkwinkel, 2019)
The article describes what kind of meaning the Polish poet Zbigniew Herbert drew from his many encounters with the Netherlands, its 17th-century painting, its history and a specific form of social norms. It provides the reader with a closer look at the subjective vision of Dutch culture presented by Herbert in the volume of essays, Still Life with a Bridle. It indicates that the poet has constructed a kind of utopia here, describing, among other things, the role of the artist and his commitment to society, and it confronts the poet’s vision with the opinions of contemporary art historians. Finally, it discusses two of Herbert’s unfulfilled intentions: books devoted to the works of Vermeer and Rembrandt, as well as reconstructing the chronology of Herbert’s subsequent journeys to the Netherlands: from 1967 to 1994.